Pencegahan Perundungan Anak Berbasis Edukasi Perlindungan Hukum Islam Di Sekolah - Hadi, Abdul; Hani, Umi; Purnomo, Agus (At Taawun Bangun Bangsa, 2025)
Bullying behavior continues to haunt Indonesian children over time. Cases of bullying are widespread among children, particularly occurring in school environments and residential areas. In Indonesia, bullying cases frequently take place within educational institutions. This is supported by data from the National Commission for Child Protection, which reported that 2011 recorded the highest number of bullying cases in schools and residential environments, with 339 cases of violence, 82 of which resulted in death. This program aims to identify bullying behavior among adolescents and to implement interventions through educational and group-based processes in Tanjung Pagar Village, North Banjarmasin District, Banjarmasin City. The activity design includes mapping, education, poster creation, games, and film screenings. Data collection instruments utilized questionnaires. The data collection techniques involved identifying bullying behavior among adolescents, followed by interventions in the form of education, group processes, poster creation, and film screenings. The data were analyzed using descriptive analysis.